(untitled) (International Current Pharmaceutical Journal, 2018)
In the present experimental investigation an attempt has been made to assess the utility of Crushed Puffed Rice (CPR)-High Molecular Weight Chitosan (HMWCH)-Hydroxypropyl Methylcellulose K15M (HPMC K15M) as a polymeric carrier for the sustained stomach delivery of Piroxicam (PRX). A total of nine formulations were prepared by using 3 (2) Taguchi factorial design, physically blending drug and polymer(s) followed by encapsulation into hard gelatin capsules size 1. The prepared capsules were evaluated for various performance such as weight variation, drug contents, in vitro buoyancy and drug release in 0.1 M HCl. The effect of drug loading on in vitro performance of the formulations was also determined. Crushed puffed rice (CPR) remained buoyant for up to average time span of 06 hr as an unwetted irregular mass in 0.1 M HCl. However, when combined with HMWCH or HPMC K15M or HPMC K15M + HMWCH a low -density cylindrical raft type hydrogel was formed which remained buoyant for up to 12 hr and released up to 99% drug in a sustained manner from 8 to 12 hr following zero order release kinetics. It was also observed that drug release from drug + CPR matrices followed Fickian mechanism. Combination of CPR + HMWCH or HMWCH + HPMC K15M also follows Fickian mechanism. Obtained data from the research work suggests that CPR in combination with HMWCH or HPMC K15M or HPMC has sufficient potential to be used as a carrier for stomach specific delivery of gastric irritant drug like PRX. Soni et al., International Current Pharmaceutical Journal, April 2018, 6(11): 61-80 http://www.icpjonline.com/documents/Vol6Issue11/01.pdf